$$\int^{\infty}_{-\infty}\frac{\sin(ax)}{x(x^2+1)}dx=\pi(1-e^{-a}), \ a\ge0$$

I tried to solve but came up with $\pi(2-e^{-a}) $. Could you tell me where did I do the mistake?

if $x=z$ then $dz=dx$

$$\int_\gamma \frac{e^{iaz}}{z(z^2+1)}\quad and\quad z(z+i)(z-i)=0\quad \rightarrow z=0,z=\pm i$$

for $ z=0$ $$Res(f,0)=\lim_{z\to 0}\frac{z.e^{iaz}}{z(z^2+1)}=1$$

for $z=1$

$$Res(f,i)=\lim_{z\to i}\frac{(z-i).e^{iaz}}{z(z+i)(z-i)}=\lim_{z\to i}\frac{e^{iaz}}{z(z+i)}=\frac{e^{-a}}{-2}$$

$$\int_\gamma \frac{e^{iaz}}{z(z^2+1)}=\int_{-R}^{R}\frac{e^{iax}}{x(x^2+1)}dx+\int_\gamma \frac{e^{iaz}}{z(z^2+1)}=\pi i(1-\frac{e^{-a}}{-2})$$

$$\int_{-R}^{R}\frac{e^{iax}}{x(x^2+1)}=\int^{R}_{-R}\frac{\cos(ax)}{x(x^2+1)}dx+i\int_{-R}^R \frac{\sin(ax)}{x(x^2+1)}=i(2\pi - 2\pi \frac{e^{-a}}{2})$$

$$\rightarrow \int_{-R}^R\frac{\sin(ax)}{x(x^2+1)}=2\pi -2\pi \frac{e^{-a}}{2}=\pi(2-e^{-a}) $$

  • 3
    $\begingroup$ Your problem is that the pole in $z=0$ belongs to $[-R,R]$ so you cannot use the residue theorem here. $\endgroup$ – Tom-Tom Jan 14 '14 at 10:27
  • 2
    $\begingroup$ An approach is to make the pole at zero disappear, considering $f(z)=(\mathrm e^{\mathrm iaz}-1)/(z(z^2+1))$. The imaginary part still yields the desired integral. Completing the loop by upper halfcircles, one is left with a unique pole at $\mathrm i$, with residue $\frac12(1-\mathrm e^{-a})$. This assumes the contribution of the upper halfcircle part disappears when $R\to+\infty$, which happens when $a\geqslant0$. $\endgroup$ – Did Jan 14 '14 at 10:32
  • $\begingroup$ @lyme Plot the function $\dfrac{sin(ax)}{x(x^2-1)}$ for $a=1$. You can guess from this picture that the integral must be positive. But the formula you have $\pi(1-e^a)$ gives a negative value. This suggest that there is something wrong with your formula. $\endgroup$ – Braindead Jan 15 '14 at 0:26

The integral depends on the value of $a$, which I assume is a real number.

Assuming that $a\ge 0$, You can use this kind of contour to integrate $f(z) = \dfrac{e^{iaz}}{z(z^2+1)}$. The point is that you have to go around the singularity at $z=0$. (An alternative is to follow Did's suggestion).

Using this contour, you obtain:

$$2\pi i Res(f,i) = \left(\int_R - \int_\epsilon\right) + \left(\int_r^R f(x) dx + \int_{-R}^{-r} f(x) dx\right),$$

$\int_R$ and $\int_\epsilon$ both represent integral of $f$ over the respective semicircles. A quick computation shows that $R\to \infty$ makes $\int_R\to 0$ and $\epsilon \to 0$ makes $\int_\epsilon\to i\pi$.


$$2\pi i Res(f,i) = - i\pi + \int_{-\infty}^\infty f(x) dx$$

Computing the residue and solving for the integral gives:

$$ \int \dfrac{\sin(ax)}{x(x^2+1)} dx = \pi (1-e^{-a})$$

For $a<0$, you can use a similar contour, but it has to be upside down from the one used above in order for the big $R$ contour to vanish as $R\to \infty$. The answer comes out to be $\pi (e^a -1)$.


I will assume $a > 0$. Call the integral $I(a)$. Differentiate w.r.t. $a$, $$ I'(a) = \int_{-\infty}^{\infty} \frac{\cos(a x)}{1+x^2} \ \mathrm{d}x = 2\int_{0}^{\infty}\frac{\cos(a x)}{1+x^2} \ \mathrm{d}x,$$ then note that $$\mathcal{L}(I'(a)) = 2\int_{0}^{\infty}\int_{0}^{\infty} \frac{\cos(a x)}{1+x^2}\exp(-as) \ \mathrm{d}a \ \mathrm{d}x,$$ $$\mathcal{L}(I'(a)) = 2\int_{0}^{\infty} \frac{s}{(x^2+s^2)(1+x^2)} \ \mathrm{d}x.$$ Using partial fractions and integrating, $$\mathcal{L}(I'(a)) = \frac{\pi}{s+1},$$ taking the inverse transform gives $$ I'(a) = \pi \mathrm{e}^{-a}, $$ integrate to obtain $$ I(a) = -\pi \mathrm{e}^{-a} + c, $$ and using $I(0) = 0$, we see that $c=\pi$ and $$ I(a) = \pi(1-\mathrm{e}^{-a}). $$

  • $\begingroup$ Watch out: the derivation of the formula for $I'(a)$ was for $a > 0$, so observing $I(0) = 0$ doesn't immediately tell you the value of $c$ unless you verify that $I(a) \rightarrow 0$ as $a \rightarrow 0^+$. To show that, write $I(a) = 2\int_0^\infty \sin(ax)/(x(x^2+1))dx$ and then use the inequality $|\sin(ax)| \leq ax$ for $x \geq 0$ to see that $|I(a)| \leq 2a\int_0^\infty dx/(x^2+1)$ for $a > 0$. Now let $a \rightarrow 0^+$ in the equation $I(a) = c - \pi{e}^{-a}$ to conclude that $0 = c - \pi$, so $c = \pi$. $\endgroup$ – KCd Jan 25 '14 at 23:33
  • $\begingroup$ That is very true. Thanks for calling me out on that! I did consider that I needed a limiting approach, but I generally write answers without any paper next to me, and I was too lazy :P. Thanks for correcting the error. $\endgroup$ – Bennett Gardiner Jan 25 '14 at 23:41

$\newcommand{\+}{^{\dagger}} \newcommand{\angles}[1]{\left\langle\, #1 \,\right\rangle} \newcommand{\braces}[1]{\left\lbrace\, #1 \,\right\rbrace} \newcommand{\bracks}[1]{\left\lbrack\, #1 \,\right\rbrack} \newcommand{\ceil}[1]{\,\left\lceil\, #1 \,\right\rceil\,} \newcommand{\dd}{{\rm d}} \newcommand{\down}{\downarrow} \newcommand{\ds}[1]{\displaystyle{#1}} \newcommand{\expo}[1]{\,{\rm e}^{#1}\,} \newcommand{\fermi}{\,{\rm f}} \newcommand{\floor}[1]{\,\left\lfloor #1 \right\rfloor\,} \newcommand{\half}{{1 \over 2}} \newcommand{\ic}{{\rm i}} \newcommand{\iff}{\Longleftrightarrow} \newcommand{\imp}{\Longrightarrow} \newcommand{\isdiv}{\,\left.\right\vert\,} \newcommand{\ket}[1]{\left\vert #1\right\rangle} \newcommand{\ol}[1]{\overline{#1}} \newcommand{\pars}[1]{\left(\, #1 \,\right)} \newcommand{\partiald}[3][]{\frac{\partial^{#1} #2}{\partial #3^{#1}}} \newcommand{\pp}{{\cal P}} \newcommand{\root}[2][]{\,\sqrt[#1]{\vphantom{\large A}\,#2\,}\,} \newcommand{\sech}{\,{\rm sech}} \newcommand{\sgn}{\,{\rm sgn}} \newcommand{\totald}[3][]{\frac{{\rm d}^{#1} #2}{{\rm d} #3^{#1}}} \newcommand{\ul}[1]{\underline{#1}} \newcommand{\verts}[1]{\left\vert\, #1 \,\right\vert} \newcommand{\wt}[1]{\widetilde{#1}}$ $\ds{\int_{-\infty}^{\infty}{\sin\pars{ax} \over x\pars{x^{2} + 1}}\,\dd x =\pi\sgn\pars{a}\pars{1 - \expo{-\verts{a}}}:\ {\large ?}.\qquad a \in {\mathbb R}}$

\begin{align} &\color{#00f}{\large\int_{-\infty}^{\infty}{\sin\pars{ax} \over x\pars{x^{2} + 1}} \,\dd x} =a\int_{-\infty}^{\infty}{1 \over x^{2} + 1}\, \color{#c00000}{\sin\pars{ax} \over ax}\,\dd x \\[3mm]&=a\int_{-\infty}^{\infty}{1 \over x^{2} + 1}\, \pars{\color{#c00000}{\half\int_{-1}^{1}\expo{\ic kax}\,\dd k}}\,\dd x =\half\,a\int_{-1}^{1}\pars{% \int_{-\infty}^{\infty}{\expo{\ic\verts{ka}x} \over x^{2} + 1}\,\dd x}\,\dd k \\[3mm]&=\half\,a\int_{-1}^{1}\pars{% 2\pi\ic\,{\expo{\ic\verts{ka}\ic} \over 2\ic}}\,\dd k =\half\,\pi a\int_{-1}^{1}\expo{-\verts{ka}}\,\dd k =\pi a\int_{0}^{1}\expo{-\verts{a}k}\,\dd k \\[3mm]&=\pi a\,{\expo{-\verts{a}} - 1 \over -\verts{a}} =\color{#00f}{\large\pi\sgn\pars{a}\pars{1 - \expo{-\verts{a}}}} \end{align}


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.